The welfare of animals used in research : practice and ethics - Hubrecht, R. (UFAW animal welfare series., 2014)
The Welfare of Animals used in Research: Practice and Ethics gives a complete and balanced overview of the issues surrounding the use of animals in scientific research. The focus of the book is on the animal welfare implications and ethics of animals in research. It covers the topics with sufficient depth to show a real understanding of varied and complex subjects, but conveys the information in a beautifully reader-friendly manner. Key features: Provides those who are not working in the field with a reasonable understanding as to why and how animals are used in res.